2008
DOI: 10.7238/rusc.v5i1.321
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ICT on Student Performance in Higher Education: Direct Effects, Indirect Effects and Organisational Change

Abstract: The purpose of the present paper is to examine the relationship between the use of information and communication technologies (ICT) and student performance in higher education. So far, economic research has failed to provide a clear consensus on the effect of ICT investments on student's achievement. Our paper aims to summarise the main findings of the literature and to give two complementary explanations. The first explanation focuses on the indirect effects of ICT on standard explanatory factors. Since a stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 37 publications
6
75
0
7
Order By: Relevance
“…Blended learning will be implemented using Bricolage approach model. The researcher attempted to answer the following research questions: (1) …”
Section: F Goal and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blended learning will be implemented using Bricolage approach model. The researcher attempted to answer the following research questions: (1) …”
Section: F Goal and Research Questionsmentioning
confidence: 99%
“…Teaching and learning requires financial stability for universities as a learning organization [1]. The advent of technological advancement in education requires tremendous cost and the most barrier to learning as cited by [2].…”
Section: Introductionmentioning
confidence: 99%
“…TIK telah menjadi alat utama pada dunia pendidikan saat ini [1], tidak saja dimanfaatkan untuk mendukung proses belajar mengajar, namun juga untuk meningkatkan manajemen pengelolaan dan administrasi pendidikan [2], [3], [4].…”
Section: Pendahuluanunclassified
“…Related to the statement above, about the use of technology on learning, a study done by Kulik (1994 as cited in Youssef & Dahmani, 2008) showed that the use of ICT by students on learning, especially the involvement of ICT-based instruction, made students earn higher score than those who did not use computer. However, it was also found that one of the certified teachers rarely used media on teaching-learning process.…”
Section: Professional Competencementioning
confidence: 99%